Soil organic carbon in agricultural systems of six countries in East Africa – a literature review of status and carbon sequestration potential - Namirembe, Sara; Piikki, Kristin; Sommer, Rolf; Söderström, Mats; Tessema, Bezaye; Nyawira, Sylvia (International Center for Tropical Agriculture, 2020)
A systematic literature review of existing evidence on soil organic carbon (SOC) responses to agronomic best management practices (BMPs) in cultivated soils of East Africa, focusing on Ethiopia, Kenya, Rwanda, Tanzania, Uganda, and Burundi. Examining current evidence on the extent to which BMPs can increase SOC stocks and whether net SOC sequestration is attainable in this region. The study also sought to identify knowledge gaps and make recommendations for future research. Independent variables: • Annual rainfall (mm year-1), as semi-arid (<600), sub-humid (601-1200), moist sub-humid (1201-1500), or humid (>1500) • Temperature • Location, • Altitude - lowland (<1500 m above sea level (a.s.l.)) or highland (≥ 1500 m a.s.l.). • Soil characteristics – type, bulk density, texture • The time period after which changes in SOC were measured - short-term (<10 years), medium-term (10-25 years), and long-term (>25 years). • Soil depth: 0-30 cm, 0-50 cm, and 0-100 cm. Dependent variables • Soil organic carbon stock (t C ha 1) • Soil organic carbon sequestration (t C ha 1 year-1) • Soil organic carbon loss (t C ha 1 year-1) (2020-02-20)